1995
DOI: 10.1016/0014-5793(95)00766-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of κ‐ and δ‐opioid receptor transcripts in immune cells

Abstract: To investigate the role of opioids as direct modulators of the immune response, we have searched for expression of the recently cloned 6,/~ and K opioid receptors in immune cells. We have devised a reverse transcriptase-polymerase chain reaction strategy which specifically detects a region spanning putative transmembrane regions 2 to 7 for each transcript in both human and mouse immune cells. In human peripheral blood lymphocyte and monocyte preparations, 6 was undetectable while the g transcript was present. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(65 citation statements)
references
References 36 publications
2
60
0
3
Order By: Relevance
“…By using RT-PCR, Gaveriaux et al [14] found that delta opioid receptor (DOR) transcripts were detectable at low levels in human T and monocyte cell lines and at high levels in human B cell lines, but were undetectable in human peripheral blood lymphocyte and monocyte populations. Recently, it was reported that DOR mRNA was detectable in CD4 ϩ and CD8 ϩ T cells purified from concanavalin A-stimulated murine splenocytes [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…By using RT-PCR, Gaveriaux et al [14] found that delta opioid receptor (DOR) transcripts were detectable at low levels in human T and monocyte cell lines and at high levels in human B cell lines, but were undetectable in human peripheral blood lymphocyte and monocyte populations. Recently, it was reported that DOR mRNA was detectable in CD4 ϩ and CD8 ϩ T cells purified from concanavalin A-stimulated murine splenocytes [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…Genes encoding these receptors are referred as to MOR (), DOR (␦), and KOR (). Their mRNAs are largely distributed throughout the nervous system (16) and some reports indicate detectable expression in immune cells also (17,18), suggesting that they are targets for direct action. The implication of these cloned opioid receptors in opiate immunomodulation in vivo however has not been demonstrated.…”
mentioning
confidence: 99%
“…Opioid receptors are constitutively expressed in non-neuronal sites including vascular endothelial cells (Cadet et al, 2000 andSaeed et al, 2000), on immune cells such as macrophages and lymphocytes (Gavériaux et al, 1995), and keratinocytes (Bigliardi et al, 2002). A role for neuronal opiates has also been shown for reduction of inflammation (for review see Machelska and Stein, 2003).…”
Section: Anti-inflammatory Effects and Tissue Protection By Hsv-enk Tmentioning
confidence: 99%